The Journals on the Domestic Lists of the IX Section of the Hungarian Academy of Sciences in Light of the Requirements of International Journal Selection - Sasvári, Péter; Urbanovics, Anna (Public Finance Quarterly, 2019)
Publish or Perish places researchers under increasing pressure, but 20 percent of the publications receive more than 80 percent of the citations according to Garfield’s Law of Concentration. The international indexing databases Scopus and the Web of Science try to index all the relevant publications. Being indexed by these databases must be a priority for Hungarian journals. The present study aims to analyse the journals on the domestic lists of the IX Section of the Hungarian Academy of Sciences. We use descriptive statistical analysis to explore the most important indicators. Our results show that 80 percent of the journals have their own website, half of them are published on time, one fifth have an archiving policy and one tenth have a code of ethics. On average, 42 months have passed since the publication of the most recent issue. These indicators depend on the quality categories, and there is a significant correlation between the category, the number of papers and the number of citations per paper.